Wiara jako akt poznawczy. Analiza "Quaestiones" Ambrozjastra - Grzegorz Babiarz (Vox Patrum, 2014)
Ambrosiaster uses two forms for the definition of the concept of faith. The first one – in the sense of a noun: fides; the second one – from the perspective of the knowing subject: credere. Abraham’s act of faith, whose object is God, is shown as a cognitive model. The acceptance of God’s authority leads to recognizing in Christ the Son of God. Believers receive in Baptism the gift the Holy Spirit and knowing the will of God. By participating in the fullness of His life, they are given access to the Eucharist. Knowability is one of God’s characteristics. Accepting this fact and submitting oneself to God’s guidance results in knowing the Trinity. Christ’s confidence in the Father is the basic principle of knowing through faith, and this translates into absolute certainty of the truthfulness of the conclusions. It is a duty of believers to explore the truth. The Gospel, interpreted by the authority of the Church, remains the main source of revelation. The intensity of cognition influences the entirety of one’s life, manifests itself in the acceptance of all the truths of the faith and in creating harmony between faith and the virtues of love and hope.